Hydroxyapatite and β-TCP modified PMMA-TiO2 and PMMA-ZrO2 coatings for bioactive corrosion protection of Ti6Al4V implants - Harb, Samarah V. [UNESP]; Bassous, Nicole J.; de Souza, Thiago A.C. [UNESP]; Trentin, Andressa [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP]; Webster, Thomas J.; Lobo, Anderson O.; Hammer, Peter [UNESP] (Elsevier, 2020)
Organic-inorganic hybrid coatings deposited on different types of metallic alloys have shown outstanding anticorrosive performance. The incorporation of osteoconductive additives such as hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP) into organic-inorganic hybrid coatings is promising to improve the osseointegration and corrosion resistance of Ti6Al4V alloys, which are the most widely used metallic orthopedic and dental implant materials today. Therefore, this study evaluated the capability of poly(methyl methacrylate) (PMMA)-TiO2 and PMMA-ZrO2 hybrid coatings modified with HA and β-TCP to act as bioactive and corrosion protection coatings for Ti6Al4V alloys. In terms of cell growth and mineralization, osteoblast viability, Ca+2 deposition and alkaline phosphatase assays revealed a significant improvement for the HA and β-TCP modified coatings, compared to the bare alloy. This can be explained by an increase in nanoscale roughness and associated higher surface free energy, which lead to enhanced protein adsorption to promote osteoblast attachment and functions on the coatings. The effect of HA and β-TCP additives on the anticorrosive efficiency was studied by electrochemical impedance spectroscopy (EIS) in a simulated body fluid (SBF) solution. The coatings presented a low-frequency impedance modulus of up to 430 GΩ cm2, 5 decades higher than the bare Ti6Al4V alloy. These findings provide clear evidence of the beneficial role of HA and β-TCP modified hybrid coatings, improving both the biocompatibility and corrosion resistance of the Ti6Al4V alloy.
Keywords: Bioactive coating; Corrosion protection; Nanocomposite coating; Organic-inorganic hybrid; Ti6Al4V alloy